A squared + B squared = c squared. c is across from the right angle and you subtract A from C and that's your answer
When you divide b squared by b squared, you are essentially dividing like terms. The rule of exponents states that when you divide like bases, you subtract the exponents. In this case, b squared divided by b squared simplifies to b^(2-2) which equals b^0. Any non-zero number raised to the power of 0 is equal to 1. Therefore, b squared divided by b squared equals 1.
b to the fourth power
Really you don't have enough data to calculate this.The height is not necessarily one of the three sides. The height is perpendicular to the width.If the triangle has a right angle, and you know two of the sides, you can calculate the third side using the rule of Pythagoras (a squared + b squared = c squared).Really you don't have enough data to calculate this.The height is not necessarily one of the three sides. The height is perpendicular to the width.If the triangle has a right angle, and you know two of the sides, you can calculate the third side using the rule of Pythagoras (a squared + b squared = c squared).Really you don't have enough data to calculate this.The height is not necessarily one of the three sides. The height is perpendicular to the width.If the triangle has a right angle, and you know two of the sides, you can calculate the third side using the rule of Pythagoras (a squared + b squared = c squared).Really you don't have enough data to calculate this.The height is not necessarily one of the three sides. The height is perpendicular to the width.If the triangle has a right angle, and you know two of the sides, you can calculate the third side using the rule of Pythagoras (a squared + b squared = c squared).
(a+b)2
a squared - b squared = (a+b)(a-b)
A squared + B squared = c squared. c is across from the right angle and you subtract A from C and that's your answer
he made the theorem C squared = A squared + B squared and A squared = C squared - B squared or B squared = C squared - A squared
a(squared)+b(squared)=c(squared) The largest number is the c, and you can choose the a and b, since you need to find the a or the b. For example: You have the numbers 3, and 5 and you needed to find b. a(squared+b(squared)=c(squared) 3(squared)+b(squared)=5(squared) 9+b(squared)=25 -9 -9 b(squared)=16 Then take the square root b=4
It is: 2b squared
It is b*b
if you mean a right triangle then the formula is a squared + b squared = c squared. a and b are the legs and c is the hypotunese. the legs are the smallest number then the hypotenese. An example is a=3 , b= ? and c =5 use the formula : a squared + b squared = c squared 3 squared + b squared = 5 squared 9 + b squared = 25 -9 - 9 _________________________________________ b squared = 16 Then you have to take the squared root of 16 which is 4 and 4 is b squared.
b to the fourth power
b= 10
b = 14324.80366
B squared equals c squared minus a squared then to find B take the square root of you answer for b squared
Really you don't have enough data to calculate this.The height is not necessarily one of the three sides. The height is perpendicular to the width.If the triangle has a right angle, and you know two of the sides, you can calculate the third side using the rule of Pythagoras (a squared + b squared = c squared).Really you don't have enough data to calculate this.The height is not necessarily one of the three sides. The height is perpendicular to the width.If the triangle has a right angle, and you know two of the sides, you can calculate the third side using the rule of Pythagoras (a squared + b squared = c squared).Really you don't have enough data to calculate this.The height is not necessarily one of the three sides. The height is perpendicular to the width.If the triangle has a right angle, and you know two of the sides, you can calculate the third side using the rule of Pythagoras (a squared + b squared = c squared).Really you don't have enough data to calculate this.The height is not necessarily one of the three sides. The height is perpendicular to the width.If the triangle has a right angle, and you know two of the sides, you can calculate the third side using the rule of Pythagoras (a squared + b squared = c squared).